Rural Education and Autonomy: community development and pedagogy of participation in the Settlement of the Landless Movement [MST], Luís Inácio Lula da Silva (Lulão) - Altemar Felberg; Geovani de Jesus Silva (Revista Brasileira de Educação do Campo, 2018)
This article seeks to present the role of Rural Education in the process of training autonomous subjects, based on a study carried out in a settlement of the Landless Movement in the South of Bahia, which sought to understand how development indicators reflect the degree Autonomy of its residents. The research was carried out through the qualitative research, with the questionnaire, semi-structured interviews and focus groups as instruments of information collection. Here autonomy is defined as the capacity of the individual to govern himself, according to a law of his own, in a free and rational way, leading him to human dignity; Setting itself up as a powerful resource capable of freeing individuals not only from submission to heteronymous processes that interfere with their freedoms of choice and action, but also from the frameworks of social and economic vulnerability. Having more autonomy and acting with greater freedom of thought and action improves people's potential to take care of themselves and to influence the world - issues central to the development process. To empower autonomy, education plays a fundamental role in the universe and in the population studied, taking place in the praxis of everyday life, in the exercise of citizenship and in social participation, consolidating itself as a practice of freedom.